New content in digital repositories : the changing research landscape - Simons, Natasha; Richardson, Joanna, 1946- (Chandos information professional series., 2013)
Research institutions are under pressure to make their outputs more accessible in order to meet funding requirements and policy guidelines. Libraries have traditionally played an important role by exposing research output through a predominantly institution-based digital repository, with an emphasis on storing published works. New publishing paradigms are emerging that include research data, huge volumes of which are being generated globally. Repositories are the natural home for managing, storing and describing institutional research content. New Content in Digital Repositories explores the diversity of content types being stored in digital repositories with a focus on research data, creative works, and the interesting challenges they pose. Chapters in this title cover: new content types in repositories; developing and training repository teams; metadata schemas and standards for diverse resources; persistent identifiers for research data and authors; research data: the new gold; exposing and sharing repository content; selecting repository software; repository statistics and altmetrics. Explores the role of repositories in the research lifecycle, and the emerging context for increasing non-text based contentFocuses on the management of research data in repositories and related issues such as metadata and persistent identifiersDiscusses skills and knowledge needed by repository staff to manage content diversity.